Integrating acute coronary syndrome services through the PSC 119 platform: The LASKAR model for emergency cardiac care in Indonesia - Supriyanto; Nasronudin; Stefanus Supriyanto (Universitas Brawijaya, 2026)
Background: The management of acute coronary syndrome (ACS) has been challenged by high rates of morbidity and mortality, prolonged reperfusion times, and a significant number of cases arriving at the hospital already deceased, particularly in Tulungagung, Indonesia. In response to this issue, Rumah Sakir Umum Daerah (RSUD) Dr. Iskak, in collaboration with the local government, established the Layanan Sindroma Koronaria Akut Terintegrasi (LASKAR) in 2016. Objective: This study aimed to evaluate the implementation and outcomes of LASKAR for emergency cardiac management and its impact on the ACS burden in low-resource settings. Methods: A comparative before-and-after design was utilized in this study. Data were collected from hospital reports, 119 logs from the Public Safety Center (PSC), and ACS registries between 2016 and 2019. The data were analyzed using a Chi-square test in JASP to assess the relationship between changes in ACS-related outcomes and the implementation of LASKAR. Result: The results demonstrated significant improvements in the management of ACS. Clinical outcomes improved concurrently, with the rate of Primary Percutaneous Coronary Intervention (PCI) more than doubling, increasing from 14.9% to 37.8% (p<0.001), while in-hospital mortality significantly decreased from 11.8% to 6.1% (p=0.007). Conclusion: Incorporating a locally developed LASKAR model into a national emergency medical platform transforms emergency cardiac care into a sustainable and effective management solution. This innovative approach not only strengthens health system responsiveness to ACS but also serves as a powerful, replicable blueprint for other low- and middle-income countries striving to elevate their healthcare capabilities.